2022
DOI: 10.1039/d2fo01442d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the harvest period on the structure and anti-allergic activity of Porphyra haitanensis polysaccharides

Abstract: With the delayed harvest period, the molecular weight and sulfate content of Porphyra haitanensis polysaccharides decreased and their anti-allergic activity increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“… Fraction Extraction method Purification process Yield of polysaccharides Monosaccharide composition Molecular weight Backbone or linkages Ref. PHP0.5–1-UF, PHP1.0–1-UF Thermal extraction, 80 °C hot water at ratio of 20:1 (w/v) for 2 h DEAE-Sepharose FF Sephacryl S-400 HR 37.1%, 48.6% 6.68 × 10 6 Da 1.14 × 10 6 Da ( Chen, Xu, et al, 2021 ) PHPs Thermal extraction, 80 °C hot water material to water ratio of 0.04, for 3 h 20.48% galactose, glucose, and fucose (76.2:2.1:1) 6.3 × 10 5 Da ( Dong et al, 2020 ) PHPs Thermal extraction, hot water DEAE-cellulose 52 3,6-anhydrogalactose ( Liu et al, 2017 ) PHP1 PHP2 PHP3 Thermal extraction, 90 °C hot water for 4 h DEAE-cellulose 52 galactose, glucose, xylose, mannose, fructose, and glucuronic acid (98.10:0.54:0.19:0.36:0.15:0.66 94.27:3.95:0.28:0.46:0.26:0.78 96.91:1.66:0.19:0.54:0.17:0.53) 5.67 × 10 5 Da 4.14 × 10 5 Da 3.23 × 10 5 Da ( Wang, Ye, Wang, & Fu, 2022 ) PHPs Thermal extraction, 80 °C hot water at ratio of 20:1 ( w / v ) for 2 h ( Wang, Zhong, et al, 2023 ) PHP Thermal extraction, 90 °C hot water at ratio of 30:1 (w/v) for 2 h 4.10% galactose (94.85%), glucose (3.18%), mannose (1.97%) from 2.623 × 10 5 to 2.308 × 10 4 Da 1 → 3 and 1 → 4 linked Galp ( Xu et al, 2019 ...…”
Section: Preparation and Extraction Of Phpmentioning
confidence: 99%
“… Fraction Extraction method Purification process Yield of polysaccharides Monosaccharide composition Molecular weight Backbone or linkages Ref. PHP0.5–1-UF, PHP1.0–1-UF Thermal extraction, 80 °C hot water at ratio of 20:1 (w/v) for 2 h DEAE-Sepharose FF Sephacryl S-400 HR 37.1%, 48.6% 6.68 × 10 6 Da 1.14 × 10 6 Da ( Chen, Xu, et al, 2021 ) PHPs Thermal extraction, 80 °C hot water material to water ratio of 0.04, for 3 h 20.48% galactose, glucose, and fucose (76.2:2.1:1) 6.3 × 10 5 Da ( Dong et al, 2020 ) PHPs Thermal extraction, hot water DEAE-cellulose 52 3,6-anhydrogalactose ( Liu et al, 2017 ) PHP1 PHP2 PHP3 Thermal extraction, 90 °C hot water for 4 h DEAE-cellulose 52 galactose, glucose, xylose, mannose, fructose, and glucuronic acid (98.10:0.54:0.19:0.36:0.15:0.66 94.27:3.95:0.28:0.46:0.26:0.78 96.91:1.66:0.19:0.54:0.17:0.53) 5.67 × 10 5 Da 4.14 × 10 5 Da 3.23 × 10 5 Da ( Wang, Ye, Wang, & Fu, 2022 ) PHPs Thermal extraction, 80 °C hot water at ratio of 20:1 ( w / v ) for 2 h ( Wang, Zhong, et al, 2023 ) PHP Thermal extraction, 90 °C hot water at ratio of 30:1 (w/v) for 2 h 4.10% galactose (94.85%), glucose (3.18%), mannose (1.97%) from 2.623 × 10 5 to 2.308 × 10 4 Da 1 → 3 and 1 → 4 linked Galp ( Xu et al, 2019 ...…”
Section: Preparation and Extraction Of Phpmentioning
confidence: 99%
“…However, excessively high or low sulfate content may not further improve the anti-inflammatory activity of polysaccharides, indicating that an optimal sulfate content is crucial for their effectiveness [117]. For example, a study on the polysaccharides obtained from Porphyra haitanensis at different growth periods found that polysaccharide samples from early harvests had higher sulfate content and molecular weights than those from late harvests, but the polysaccharides had lower anti-allergic activity than the latter [118].…”
Section: Functional Groupsmentioning
confidence: 99%